ANALYSIS OF RISK FACTORS FOR OBESITY IN WOMEN AGED 15-49 YEARS IN SOUTH AFRICA (THE DHS PROGRAM 2016) - Sinatrya, Alfadhila Khairil; Mahmudiono, Trias; Melaniani, Soenarnatalina (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2023)
Overweight and obesity can be interpreted as abnormal fat accumulation that can cause health problems. The average BMI (Body Mass Index) in adult women has also continued to increase. This study aims to identify the relationship between age, alcohol consumption, cigarette consumption, employment status, economic status, ethnicity and area of "‹"‹residence with the incidence of obesity in women aged 15-49 years in South Africa and determine the most influential factors on obesity. This study is a quantitative study with a design cross-sectional using secondary data from The DHS Program 2016. Respondents in this study were women aged 15 - 49 years in South Africa as many as 1158 people. The dependent variable in this study is the nutritional status of obesity which is classified as obese if BMI â‰¥25 kg/m2. While the independent variables are age, alcohol consumption, cigarette consumption, employment status, economic status, ethnicity, and area of "‹"‹residence. Data were analyzed by chi-square and logistic regression. The results showed that the factors associated with obesity were age, employment status and economic status (p-value <0.05). The most influential factor is adult age with a range of 25 - 49 years. Therefore, there is a need for behavioral changes in adult women 25-49 years in South Africa and national monitoring evaluation of multisectoral programs for obesity prevention in South Africa.